Eurogin roadmap 2017: Triage strategies for the management of HPV‐positive women in cervical screening programs. Issue 4 (8th February 2018) - Cuschieri, Kate; Ronco, Guglielmo; Lorincz, Attila; Smith, Laurie; Ogilvie, Gina; Mirabello, Lisa; Carozzi, Francesca; Cubie, Heather; Wentzensen, Nicolas; Snijders, Peter; Arbyn, Marc; Monsonego, Joe; et al.
Abstract : Cervical cancer screening will rely, increasingly, on HPV testing as a primary screen. The requirement for triage tests which can delineate clinically significant infection is thus prescient. In this EUROGIN 2017 roadmap, justification behind the most evidenced triages is outlined, as are challenges for implementation. Cytology is the triage with the most follow‐up data; the existence of an HR‐HPV‐positive, cytology‐negative group presents a challenge and retesting intervals for this group (and choice of retest) require careful consideration. Furthermore, cytology relies on subjective skills and while adjunctive dual‐staining with p16/Ki67 can mitigate inter‐operator/‐site disparities, clinician‐taken samples are required. Comparatively, genotyping and methylation markers are objective and are applicable to self‐taken samples, offering logistical advantages including in low and middle income settings. However, genotyping may have diminishing returns in immunised populations and type(s) included must balance absolute risk for disease to avoid low specificity. While viral and cellular methylation markers show promise, more prospective data are needed in addition to refinements in automation. Looking forward, systems that detect multiple targets concurrently such as next generation sequencing platforms will inform the development of triage tools. Additionally, multistep triage strategies may be beneficial provided they do not create complex, unmanageable pathways. Inevitably, the balance of risk to cost(s) will be key in decision making, although defining an acceptable risk will likely differ between settings. Finally, given the significant changes to cervical screening and the variety of triage strategies, appropriate education of both health care providers and the public is essential.